Hermeneutic and feminism: a version of the original - Millán Muñío, Mª Ángeles (Ondina - Ondine, 2020)
Childhood is a privileged time to build sexuality, and the readings and images acquired at that age make the first layer of the palimpsest of our gender identity. Children´s tales are discursive means that can always be transformed and adapted according to the ideology that rules the society in each moment and even governs the original and its version. In this regard, feminist epistemology presents itself as an indispensable tool of reflection on porpuse of the binary categories of masculinity and femininity that go through all social order. Key words: Original/version, children´s tales, sexual difference, identity, masculinity/femininity.